Galectin-3 as a potential biomarker of microvascular complications in patients with Type 2 diabetes - Surendra Kumar; Chandrapal S Ranawat; Chandrashekhar Bhandiwad; Harish Arya; Manoj Mali; Chandreshwar P Singh; Nitin Sharma; Navneet Lathwal; Sayad Wasim (Indian Journal of Endocrinology and Metabolism, 2022)
Introduction: Human Galectin-3 is a 32- to 35-kDa size lectin, mainly comprises a C-terminal carbohydrate recognition binding domain (CRD) and N-terminal domain. It acts as a powerful pro-inflammatory signalling factor, which plays an important role in the activation, chemotaxis, and cytokine release of inflammatory cells. Galectin-3 has also been studied in relation to development of insulin resistance. The levels of galectin-3 have been observed to be associated with both diabetes prevalence and incidence, independent of traditional diabetes risk factors. It is also associated with development of microvascular complications of diabetes mellitus like retinopathy, nephropathy and neuropathy. Methods: Tertiary care hospital-based cross-sectional prospective study. 150 patients selected by simple random sampling and were divided into 3 groups., Group A – Patients of Type 2 Diabetes mellitus without microvascular complications (n=50), Group B – patients of Type 2 diabetes mellitus with microvascular complications (n=50) and Group C - Healthy control (n=50) Statistical Analysis: Descriptive statistics was performed by calculating mean and standard deviation for the continuous variables. chi-square goodness-to-fit test, Student T test (unpaired) and Analysis of variance (ANOVA) and multivariate analysis were used to compare means. The p-value was taken significant when less than 0.05 (P<0.05) and a confidence interval of 95%. Results: In group A, B and C majority of patients were between 56-60 years with 34%, 40% and 36% cases, respectively. The mean BMI shows that the Patients with complications had significantly higher BMI than those without complications and controls had significantly lower BMI than patients having diabetes. The data shows statistical significance with deranged biochemical profile in patients with DM with complications as compared to patients without complications and control group. In both groups A and B patients with HbA1c between 9.1-12 had mean serum galectin level (20.2 in group A, 25.9 in group B) significantly higher than patients with HbA1c between 6.5-9 (18.5 in group A and 20.4 in group B). patients with deranged lipid profile had significantly higher serum galectin level in all 3 groups, with cases from group B having higher values than group A. While controls had the lowest value of serum galectin (P value<0.001). There was a highly significant correlation between high serum galectin levels and the incidence of both non-progressive and progressive retinopathy (P value=0.0001). The mean galectin of patients with neuropathy was 28.3 ± 3.1 ng/ml, which was significantly higher than patients from group B without neuropathy (24.5 ± 2.6 ng/ml). The mean serum galectin level of patients with macroalbuminuria was 30.1± 1.3 ng/ml which was significantly higher than those with microalbuminuria having mean galectin level of 22.8 ±4.8 ng/ml. There was a highly significant correlation between high serum galectin levels and the incidence of both micro and macroalbuminuria (P value=0.0001). Conclusion: This study concludes that elevated serum Galectin-3 levels are associated with diabetes-related chronic inflammatory processing pathway, and closely relates to the severity of diabetes in T2DM both with and without complications. Therefore, Galectin-3 may be helpful in the diagnosis and prognosis of microvascular and macrovascular complications in T2DM patients.